Numerical study of gas-liquid flow maldistribution in a T-junction having very small diameter ratio - Saieed, A. (Institute of Electrical and Electronics Engineers Inc., 2018)
Industries have been using T-junctions for either combining or dividing incoming fluids for decades. A flow phenomena termed as phase maldistribution have caused oil and gas industries to use T-junctions as partial multiphase separators. This is because, a T-junction can reduce the load on main separators by partly separating the gas from the multiphase flow coming from an oil well. From the previously published research, it was found that liquid phase superficial velocity have an inverse relationship with liquid carryover. However, to the best of author's knowledge, all of these investigations were focused on T- junctions with diameter ratios between 1 and 0.2. Likewise, most of these studies were performed on fully horizontal T-junctions. Previous literature also states that decreasing the diameter ratio increases the phase separation performance of a T-junction. However, a couple of sources reported that in very small diameter ratio T-junctions, liquid carryover becomes very sensitive to side arm extraction rates. This ultimately cause liquid carryover to suddenly increase at high extraction rates. Therefore, a numerical study is carried out in order to understand the effect of liquid superficial velocity on liquid carryover in a 0.167 diameter ratio T-junction having a vertically upward side. For this study, simulations were performed on 1 and 0.167 diameter ratio T- junctions under air-water stratified flow conditions. Results from 1 diameter ratio T-junctions were used to validate present model by comparing it with previously reported experimental data. The results obtained from 0.167 diameter ratio T-junction depicts that higher the liquid phase velocity, less will be the liquid carryover. However, liquid carryover is relatively quite large in 0.167 diameter ratio T-junction as compare to 1 diameter ratio T-junction under stratified flow conditions. Â© 2017 IEEE.